Diagnostic value of matrix metalloproteinase-9 in the course of osteoarthritis in young persons with excessive body weight and obesity - A. Litvynova; L. Pasieshvili; A. Zagrebelska; T. Hadirova (Kazimierz Wielki University, 2022)
In 125 patients with osteoarthritis (OA), among whom 75 had increased body weight, the content of matrix metalloproteinase-9 (MMP-9) was studied. It was established that the course of OA is accompanied by an increase in the content of MMP-9, which correlates with the body mass index. It was proved that the activity of this enzyme did not depend on gender and age in young patients, but had a direct correlative dependence on the radiological stage of the disease. It is recommended to use this enzyme as an additional criterion for the course of osteoarthritis and control of treatment measures.